SUBSTANTIATION OF REQUIREMENTS TO R&D CONTROLLING IN TERMS OF COSTS - Y. Kafiyatullina (Вестник университета)
The development of innovation, improve the competitiveness of products, works and services are impossible without massive costs and state institutions on scientific research and experimental development (R & D). The costs allocated to research and development has a direct impact on the volume of innovative products, highlighting the need for efficient and effective use of allocated funds, the organization control over their use. The article analyzes the cost structure of R & D, the analysis of the dynamics of such costs is a list of transaction costs, justifies the choice of controlling system for the management of expenses on research and development and the list of its requirements.